2012
DOI: 10.1097/tp.0b013e31826e19e2
|View full text |Cite
|
Sign up to set email alerts
|

Concordance Among Pathologists in the Second Cardiac Allograft Rejection Gene Expression Observational Study (CARGO II)

Abstract: The 2004 revision has done little to improve agreement on the higher ISHLT grades. An EMB grade ≥2R is not by itself sufficient as a basis for clinical decisions or as a research criterion. Steps should be taken toward greater uniformity in EMB grading, and efforts should be made to replace the ISHLT classification with diagnostic criteria--EMB based or otherwise--that correspond better with the pathophysiology of the transplanted heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
129
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(133 citation statements)
references
References 12 publications
3
129
0
1
Order By: Relevance
“…Substantial interobserver variability exists in the grading of heart biopsies (2, 14), and acute rejection may be missed when taking small biopsies of myocardial tissue, owing to the inhomogeneous nature of inflammatory infiltrates and graft damage. The concordance of biopsy interpretation among cardiac pathologists was examined in the context of the CARGO II study (14): the overall, all-grade agreement was found to be 71%, and the positive agreement for biopsies assigned a grade ≥2R was less than 30%. It is possible to infer a sensitivity and a selectivity for the biopsy from these observed rates of concordance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial interobserver variability exists in the grading of heart biopsies (2, 14), and acute rejection may be missed when taking small biopsies of myocardial tissue, owing to the inhomogeneous nature of inflammatory infiltrates and graft damage. The concordance of biopsy interpretation among cardiac pathologists was examined in the context of the CARGO II study (14): the overall, all-grade agreement was found to be 71%, and the positive agreement for biopsies assigned a grade ≥2R was less than 30%. It is possible to infer a sensitivity and a selectivity for the biopsy from these observed rates of concordance.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to infer a sensitivity and a selectivity for the biopsy from these observed rates of concordance. Considering all biopsies graded 0 and 1R as negative and biopsies graded ≥2R as positive, the estimated sensitivity of biopsy is 0.58 and the selectivity is 0.96 [data in Table 1 and (14)]. In comparing our cfdDNA data with biopsy, using a threshold of 0.25%, we find a sensitivity of 0.58 and a selectivity of 0.87 (also considering 0 and 1R biopsies together as negative and ≥2R as positive).…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Endomyocardial biopsies scored according to the working formulation of 1990 were reclassified based on the revised working formulation of 2004. To avoid bias introduced by different pathologists, 34 all included samples were scored by the same team of pathologists. According to the ISHLT definition of rejection, only patients with an EMB scored as a rejection grade ≥ 2R were considered to experience a clinically relevant AR, which was treated with antirejection therapy consisting of 1 g methylprednisolone on three consecutive days.…”
Section: Study Populationmentioning
confidence: 99%
“…For instance, the AlloMap (CareDx, Brisbane, CA) can be used to reduce the frequency of biopsy without altering clinical outcomes (29). In addition, sampling error can be an issue with endomyocardial biopsy and pathological interpretation of biopsies is subject to bias and significant intra-observer variability (30, 31). We believe that [ 18 F]PET is less subject to sampling bias and provides a quantitative means to assess rejection throughout the entire graft.…”
Section: Discussionmentioning
confidence: 99%